2021
DOI: 10.1002/solr.202100842
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Atomic Layer Deposited Electron Transport Layers for Co‐Evaporated Perovskite Solar Cells

Abstract: In this work, we explore the potentials and the characteristics of electron‐transporting layers (ETL) grown by atomic layer deposition (ALD) at low temperature in co‐evaporated perovskite solar cells (PSCs). The thermal‐based ALD process has been investigated by tuning the main growing conditions as the number of cycles and the growth temperature. We show that un‐annealed ALD‐SnO2 thin films grown at temperatures between 80 °C and 100 °C are efficient ETL in n.i.p co‐evaporated MAPbI3 PSCs which can achieve po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…This thickness has been chosen as it can guarantee the highest performance in our n-i-p co-evaporated PSCs. 2,30,35,51,52 The MAPb(Br x I 1Àx ) 3 lms have been prepared by dropping the MABr solution (with a concentration of 10 mg ml À1 in IPA) on the MAPbI 3 lm and letting it reacts for a certain time interval (ranging from 1 min to 5 min) before spin-coating the lms to remove unreacted MABr/ IPA. The 3-steps process is schematized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This thickness has been chosen as it can guarantee the highest performance in our n-i-p co-evaporated PSCs. 2,30,35,51,52 The MAPb(Br x I 1Àx ) 3 lms have been prepared by dropping the MABr solution (with a concentration of 10 mg ml À1 in IPA) on the MAPbI 3 lm and letting it reacts for a certain time interval (ranging from 1 min to 5 min) before spin-coating the lms to remove unreacted MABr/ IPA. The 3-steps process is schematized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[273] Recently, Erdenebileg et al reported a co-evaporated MAPbI 3 perovskite layer with a low-temperature atomic layer deposited SnO 2 ETLs. [274] Guo et al employed SnO 2 ETL to report ambient processed planar n-i-p MAPbI 3 PSCs with high efficiency of 19.28%. They introduced MA gas to dissolve the perovskite precursor solution, which consisted of lead iodide (PbI 2 ) and methylamine iodide (MAI) in acetonitrile (ACN) solution.…”
Section: The Role Of Etl In the Performance Of Planar N-i-p Structure...mentioning
confidence: 99%
“…reported a co‐evaporated MAPbI 3 perovskite layer with a low‐temperature atomic layer deposited SnO 2 ETLs. [ 274 ]…”
Section: Common Solar Cell Structures and Their Effect On Performancementioning
confidence: 99%
“…More importantly, this method is scalable and allows precise control of the film thickness, even on textured surfaces. , The first work published in 2013 using thermal co-evaporation to deposit MAPbI 3– x Cl x reported a PCE of 15.4% for small-area devices . To date, the PCEs of perovskite solar cells based on methylammonium lead iodide (MAPbI 3 ) prepared by co-evaporation reach over 20% in both nip and pin configurations on the small-area devices and over 18% on perovskite minimodules. , …”
Section: Introductionmentioning
confidence: 99%